Preparation method and application of degradable PNIPAM / MSN hydrogel

By adding mesoporous silica (MSN) and adjusting the polymerization time during the preparation of PNIPAM hydrogel, the degradable PNIPAM/MSN hydrogel was prepared, which solved the problem of slow degradation rate of PNIPAM hydrogel in the body. Effective application in drug delivery systems and the effect of osteoarthritis treatment is achieved.

CN119391006APending Publication Date: 2025-02-07SHANGHAI INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411527813.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

PNIPAM hydrogels have a slow natural degradation rate in the body, and they need to accelerate their natural degradation process through modification or adjustment of processes to meet the needs of drug delivery systems.

Method used

Degradable PNIPAM/MSN hydrogels were prepared by adding mesoporous silica (MSN) during the preparation of NIPAM hydrogels and adjusting the polymerization time. The method is polymerized under nitrogen protection, and the appropriate amount of potassium persulfate and tetramethylethylenediamine are added to control the polymerization conditions to form a stable hydrogel.

Benefits of technology

By adding MSN and adjusting polymerization time, the natural degradation time of PNIPAM/MSN hydrogel can be effectively controlled, increasing its degradation rate in the body, suitable for drug delivery systems, and showing effective drugs in osteoarthritis treatment Delivery and therapeutic effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391006A_ABST
    Figure CN119391006A_ABST
Patent Text Reader

Abstract

The preparation method comprises the following steps: under the protection of nitrogen, mixing N-isopropylacrylamide and potassium persulfate, adding mesoporous silica and deionized water, carrying out ultrasonic treatment for 10-60 minutes, uniformly mixing, carrying out polymerization reaction for 0.5-2 hours under the constant temperature condition of 20-30 DEG C, adding tetramethylethylenediamine, carrying out ultrasonic treatment for 20-30 minutes, and carrying out ultrasonic treatment for 20-30 minutes to obtain the degradable PNIPAM / MSN hydrogel. Carrying out constant-temperature polymerization for 6 to 24 hours under the condition that the temperature is 20 to 30 DEG C, so as to obtain the degradable PNIPAM / MSN hydrogel. By adjusting the polymerization time, the natural degradation time of the sample can be regulated and controlled, the process is simple, the stability is good, the translation entropy of water molecules and ions is maximized, the LCST point is effectively controlled, and the method can be widely applied to a drug delivery system.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of hydrogels, and in particular relates to a preparation method and application of a degradable PNIPAM / MSN hydrogel. Background Art

[0002] With the advancement of technology, the field of drug delivery is developing rapidly. Poly(N-isopropylacrylamide) (PNIPAM) hydrogels are a hot topic in drug delivery due to their excellent temperature responsiveness. PNIPAM homopolymers and copolymers can be used to load drugs and cells, and even in tissue engineering. PNIPAM contains hydrophilic amide groups and hydrophobic isopropyl groups. Its lower critical temperature (LCST) is approximately 32°C, and above this critical temperature, it exhibits a sharp phase transition. Below the LCST, the polar groups form hydrogen bonds with water molecules and polymer molecules, resulting in a stretched, continuous conformation in water. Above the LCST, the hydrogen bonds within the cross-linked network of PNIPAM segments break, and the hydrophobic effect of the isopropyl groups causes water to be rapidly expelled. The hydrogel rapidly shrinks and transforms into a solid, securing it to the affected area. Compared to other warm hydrogel systems, the LCST of PNIPAM is closer to body temperature, and the LCST can be adjusted to adapt to various conditions by combining with other groups. This, to a certain extent, expands the scope and field of its application.

[0003] After the drug is delivered to the human body for release, the drug delivery carrier needs to be naturally degraded in the body. The natural degradation rate of PNIPAM in the body is slow, and the natural degradation of PNIPAM needs to be accelerated by modification or adjustment of the process. Summary of the Invention

[0004] The purpose of the present invention is to provide a method for preparing a degradable PNIPAM / MSN hydrogel.

[0005] Another object of the present invention is to provide an application of the degradable PNIPAM / MSN hydrogel prepared by the method in preparing a drug delivery system.

[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0007] The first aspect of the present invention provides a method for preparing a degradable PNIPAM / MSN hydrogel, comprising the following steps:

[0008] Under nitrogen protection, N-isopropylacrylamide (NIPAM) and potassium persulfate (KPS) with a molar ratio of 1:0.001-0.5 are mixed, mesoporous silica (MSN) and deionized water are added, and the molar ratio of mesoporous silica (MSN) and N-isopropylacrylamide (NIPAM) is 0.05-1:1. Ultrasonic mixing is performed for 10-60 minutes (preferably 30 minutes) and the mixture is kept at a constant temperature of 20-30°C (preferably 25°C). The polymerization reaction is carried out for 0.5 to 2 hours (preferably 1 hour), tetramethylethylenediamine (TEMED) is added, the molar ratio of tetramethylethylenediamine (TEMED) to N-isopropylacrylamide (NIPAM) is 0.01 to 0.3:1, and the polymerization is carried out at a constant temperature of 20 to 30° C. (preferably 25° C.) for 6 to 24 hours (preferably 9 hours, 12 hours, 15 hours, 18 hours, 24 hours) to obtain the degradable PNIPAM / MSN hydrogel.

[0009] The concentration of N-isopropylacrylamide (NIPAM) dissolved in deionized water is 0.1-1 mol / L (preferably 0.44 mol / L).

[0010] The molar ratio of N-isopropylacrylamide (NIPAM) to potassium persulfate (KPS) is 1:0.013.

[0011] The molar ratio of the mesoporous silica (MSN) to N-isopropylacrylamide (NIPAM) is 0.38:1.

[0012] The molar ratio of tetramethylethylenediamine (TEMED) to N-isopropylacrylamide (NIPAM) is 0.015:1.

[0013] The second aspect of the present invention provides a use of the degradable PNIPAM / MSN hydrogel prepared by the method in preparing a drug delivery system.

[0014] The third aspect of the present invention provides a use of the degradable PNIPAM / MSN hydrogel prepared by the method in the preparation of a drug for treating osteoarthritis.

[0015] The drug for treating osteoarthritis is a degradable PNIPAM / MSN hydrogel loaded drug, and the loaded drug is echinacoside.

[0016] Due to the adoption of the above technical solution, the present invention has the following advantages and beneficial effects:

[0017] The present invention provides a method for preparing a degradable PNIPAM / MSN hydrogel. MSNs are added to the NIPAM hydrogel during preparation, followed by mixing to form the PNIPAM / MSN hydrogel, which is then degraded in vitro on a shaker. By adjusting the polymerization time, the natural degradation time of the sample can be controlled. The method offers a simple process, excellent stability, maximizes the translational entropy of water molecules and ions, and effectively controls the liquid chromatography-stability (LCST) point, making it widely applicable in drug delivery systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 Schematic diagram of the infrared spectrum of the PNIPAM / MSN hydrogel prepared in Example 3.

[0019] Figure 2 Schematic diagram of SEM of PNIPAM / MSN hydrogel prepared in Example 3.

[0020] Figure 3 Schematic diagram of SEM of PNIPAM / MSN hydrogel prepared in Example 3 and PNIPAM hydrogel after degradation.

[0021] Figure 4 Schematic diagram of the infrared spectrum of the PNIPAM / MSN hydrogel after degradation prepared in Example 3.

[0022] Figure 5 Schematic diagram of mass change during the degradation process of PNIPAM / MSN hydrogel prepared in Examples 1 to 5.

[0023] Figure 6 Schematic diagram of CT scan of a mouse with osteoarthritis.

[0024] Figure 7 Schematic diagram of CT scan of osteoarthritis mice seven days after injection of drug-loaded PNIPAM / MSN hydrogel. DETAILED DESCRIPTION

[0025] In order to explain the present invention more clearly, the present invention will be further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive and should not be used to limit the scope of protection of the present invention.

[0026] Example 1

[0027] A method for preparing a degradable PNIPAM / MSN hydrogel comprises the following steps:

[0028] Under nitrogen, N-isopropylacrylamide (NIPAM) (4.4190 mmol, 0.5 g) and potassium persulfate (KPS) (0.0555 mmol, 0.015 g) were added to a four-necked flask. Mesoporous silica (MSN) (1.6650 mmol, 0.1 g) and 10 mL of deionized water were then added and mixed by sonication for 30 minutes. The flask was placed in a thermostatic water bath at 25°C for polymerization for 1 hour. Tetramethylethylenediamine (TEMED) (0.0667 mmol, 0.0076 g, 10 μL) was added and the reaction was continued at 25°C for 9 hours. The product was washed several times with deionized water to remove unreacted monomers, yielding 9.5130 g of degradable PNIPAM / MSN hydrogel.

[0029] Example 2

[0030] A method for preparing a degradable PNIPAM / MSN hydrogel comprises the following steps:

[0031] Under nitrogen, N-isopropylacrylamide (NIPAM) (4.4190 mmol, 0.5 g) and potassium persulfate (KPS) (0.0555 mmol, 0.015 g) were added to a four-necked flask. Mesoporous silica (MSN) (1.6650 mmol, 0.1 g) and 10 mL of deionized water were then added and mixed by sonication for 30 minutes. The flask was placed in a thermostatic water bath at 25°C for polymerization for 1 hour. Tetramethylethylenediamine (TEMED) (0.0667 mmol, 0.0076 g, 10 μL) was added and the polymerization continued at 25°C for 12 hours. The product was washed several times with deionized water to remove unreacted monomers, yielding 9.624 g of a degradable PNIPAM / MSN hydrogel.

[0032] Example 3

[0033] A method for preparing a degradable PNIPAM / MSN hydrogel comprises the following steps:

[0034] Under nitrogen, N-isopropylacrylamide (NIPAM) (4.4190 mmol, 0.5 g) and potassium persulfate (KPS) (0.0555 mmol, 0.015 g) were added to a four-necked flask. Mesoporous silica (MSN) (1.6650 mmol, 0.1 g) and 10 mL of deionized water were then added and mixed by ultrasonication for 30 minutes. The flask was placed in a thermostatic water bath at 25°C for polymerization for 1 hour. Tetramethylethylenediamine (TEMED) (0.0667 mmol, 0.0076 g, 10 μL) was added and the polymerization continued at 25°C for 15 hours. The product was washed several times with deionized water to remove unreacted monomers, yielding 9.775 g of degradable PNIPAM / MSN hydrogel.

[0035] Figure 1 This is a schematic diagram of the infrared spectrum of the PNIPAM / MSN hydrogel prepared in Example 3. It can be seen from the figure that at 1636.72 cm -1 The stretching vibration of C=C is 1611.40cm -1 The stretching vibration of NH is at 3465.50 cm -1 and 3484.91cm -1 The strong bimodal stretching vibration of the amide group at , indicated that the PNIPAM / MSN hydrogel was successfully prepared.

[0036] Figure 2 This is a SEM schematic diagram of the PNIPAM / MSN hydrogel prepared in Example 3. As can be seen from the figure, the surface of the hydrogel is relatively flat and smooth, and the MSNs are relatively evenly dispersed in the hydrogel, indicating that the porous structure of the PNIPAM / MSN hydrogel is not destroyed after the addition of MSNs.

[0037] Degradation of PNIPAM / MSN hydrogels: PNIPAM / MSN hydrogel samples were placed on a shaker for degradation. Samples were removed and weighed at regular intervals to observe weight changes. The shaker was set at 38°C and 100 rpm, and samples were removed and weighed every four days.

[0038] Figure 3 This is a SEM diagram of the PNIPAM / MSN hydrogel after degradation prepared in Example 3. As can be seen from the figure, a large number of wrinkles and powdery small particles appear on the surface of the PNIPAM / MSN hydrogel. Figure 2 Comparison reveals that the hydrogel's original structure is no longer retained after degradation, leaving only exposed MSN particles. A small amount of powder adheres to the particle surface, with uneven and small particle sizes ranging from approximately 0-5 μm. The pore edges on the surface are severely powdered, detached, and damaged, with the pores collapsing and tilting, resulting in pore shrinkage and deformation, indicating that the PNIPAM / MSN hydrogel has degraded.

[0039] Figure 4 This is a schematic diagram of the infrared spectrum of the PNIPAM / MSN hydrogel after degradation prepared in Example 3. By comparison, it can be seen that the 3400-3500 cm -1 There are double infrared absorption peaks and the peaks are more complex, 3465.50cm -1 and 3484.91cm -1 The strong double-peak stretching vibration of the amide group at the position disappeared, indicating that the amide group decomposed into various small molecular amines, further proving that the PNIPAM / MSN hydrogel was degraded.

[0040] Example 4

[0041] A method for preparing a degradable PNIPAM / MSN hydrogel comprises the following steps:

[0042] Under nitrogen, N-isopropylacrylamide (NIPAM) (4.4190 mmol, 0.5 g) and potassium persulfate (KPS) (0.0555 mmol, 0.015 g) were added to a four-necked flask. Mesoporous silica (MSN) (1.6650 mmol, 0.1 g) and 10 mL of deionized water were then added and mixed by sonication for 30 minutes. The flask was placed in a thermostatic water bath at 25°C for polymerization for 1 hour. Tetramethylethylenediamine (TEMED) (0.0667 mmol, 0.0076 g, 10 μL) was added and the polymerization continued at 25°C for 18 hours. The product was washed several times with deionized water to remove unreacted monomers, yielding 9.656 g of degradable PNIPAM / MSN hydrogel.

[0043] Example 5

[0044] A method for preparing a degradable PNIPAM / MSN hydrogel comprises the following steps:

[0045] Under nitrogen, N-isopropylacrylamide (NIPAM) (4.4190 mmol, 0.5 g) and potassium persulfate (KPS) (0.0555 mmol, 0.015 g) were added to a four-necked flask. Mesoporous silica (MSN) (1.6650 mmol, 0.1 g) and 10 mL of deionized water were then added and mixed by ultrasonication for 30 minutes. The flask was placed in a thermostatic water bath at 25°C for polymerization for 1 hour. Tetramethylethylenediamine (TEMED) (0.0667 mmol, 0.0076 g, 10 μL) was added and the reaction was continued at 25°C for 24 hours. The product was washed several times with deionized water to remove unreacted monomers, yielding 9.817 g of degradable PNIPAM / MSN hydrogel.

[0046] Degradation of PNIPAM / MSN hydrogels: PNIPAM / MSN hydrogel samples were placed on a shaker for degradation. Samples were removed and weighed at regular intervals to observe weight changes. The shaker was set at 38°C and 100 rpm, and samples were removed and weighed every four days.

[0047] Figure 5 The following is a schematic diagram of the mass change during the degradation process of the PNIPAM / MSN hydrogels prepared in Examples 1 to 5. As can be seen from the figure, as the polymerization time increases, the rate of mass change increases, the mass decreases after degradation, and the degree of degradation deepens, reaching a peak at 15 hours. After that, the degradation rate and degree begin to slow as the polymerization time increases. The polymerization time can greatly affect the degradation rate of the PNIPAM / MSN hydrogel, and the PNIPAM / MSN hydrogel degrades fastest when the polymerization time is 15 hours. A polymerization time of 15 hours can be selected for synthesis.

[0048] Example 6

[0049] A method for preparing a degradable PNIPAM / MSN hydrogel comprises the following steps:

[0050] Under nitrogen, N-isopropylacrylamide (NIPAM) (4.4190 mmol, 0.5 g) and potassium persulfate (KPS) (0.0555 mmol, 0.015 g) were added to a four-necked flask. Mesoporous silica (MSN) (1.6650 mmol, 0.1 g) and 10 mL of deionized water were then added and mixed by sonication for 30 minutes. The flask was placed in a thermostatic water bath at 25°C for polymerization for 1 hour. Tetramethylethylenediamine (TEMED) (0.0667 mmol, 0.0076 g, 10 μL) was added and the polymerization continued at 25°C for 15 hours. The product was washed several times with deionized water to remove unreacted monomers, yielding 9.798 g of degradable PNIPAM / MSN hydrogel.

[0051] Application of PNIPAM / MSN hydrogel in drug delivery system

[0052] 9.798 g of PNIPAM / MSN hydrogel was mixed with echinacoside (0.127 mmol, 0.1 g) and placed in a constant temperature shaker with the following parameters: temperature 25°C, frequency 100 r / min, and time 24 hours. The drug-loaded hydrogel was injectable and was injected into mice with osteoarthritis using a syringe. Seven days later, the osteoarthritis sites of the mice were photographed using micro-CT.

[0053] Figure 6This is a CT diagram of a mouse with osteoarthritis. As can be seen from the figure, the bones and joints are obviously damaged and have a lot of hyperplasia, and there is no obvious healing phenomenon; Figure 7 CT images of osteoarthritis mice seven days after injection with drug-loaded PNIPAM / MSN hydrogel. The images show a reduction in bone hyperplasia, a smoothing of the joint surface, and reduced swelling at the site of inflammation. This demonstrates the potential of PNIPAM / MSN hydrogels for drug delivery systems.

[0054] The above description is merely a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Although the present invention has been disclosed as a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with this patent can make slight changes or modifications to equivalent embodiments using the above technical content without departing from the scope of the technical solution of the present invention. However, any simple modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the solution of the present invention.

Claims

1. A method for preparing a degradable PNIPAM / MSN hydrogel, characterized in that: The following steps are involved: Under nitrogen protection, N-isopropylacrylamide and potassium persulfate in a molar ratio of 1:0.001-0.5 are mixed, mesoporous silica and deionized water are added, the molar ratio of mesoporous silica and N-isopropylacrylamide is 0.05-1:1, and ultrasonic mixing is performed for 10-60 minutes to mix evenly, and polymerization is performed at a constant temperature of 20-30°C for 0.5-2 hours, tetramethylethylenediamine is added, the molar ratio of tetramethylethylenediamine and N-isopropylacrylamide is 0.01-0.3:1, and constant temperature polymerization is performed at a temperature of 20-30°C for 6-24 hours to obtain the degradable PNIPAM / MSN hydrogel.

2. The method for preparing the degradable PNIPAM / MSN hydrogel according to claim 1, characterized in that: The concentration of the N-isopropylacrylamide dissolved in deionized water is 0.1-1 mol / L.

3. The method for preparing the degradable PNIPAM / MSN hydrogel according to claim 1, characterized in that: The molar ratio of the N-isopropylacrylamide to potassium persulfate is 1:0.

013.

4. The method for preparing the degradable PNIPAM / MSN hydrogel according to claim 1, characterized in that: The molar ratio of the mesoporous silica to N-isopropylacrylamide is 0.38:

1.

5. The method for preparing the degradable PNIPAM / MSN hydrogel according to claim 1, characterized in that: The molar ratio of tetramethylethylenediamine to N-isopropylacrylamide is 0.015:

1.

6. Use of the degradable PNIPAM / MSN hydrogel prepared by the method according to any one of claims 1 to 5 in preparing a drug delivery system.

7. Use of the degradable PNIPAM / MSN hydrogel prepared by the method according to any one of claims 1 to 5 in preparing a drug for treating osteoarthritis.

8. The use according to claim 7, characterized in that: The drug for treating osteoarthritis refers to a degradable PNIPAM / MSN hydrogel loaded drug, and the loaded drug refers to echinacoside.